Freshwater-adapted sea bass Dicentrarchus labrax feeding frequency impact in a lettuce Lactuca sativa aquaponics system - Stathopoulou,Paraskevi; Berillis,Panagiotis; Vlahos,Nikolaos; Nikouli,Eleni; Kormas,Konstantinos A.; Levizou,Efi; Katsoulas,Nikolaos; Mente,Eleni (PeerJ, 2021)
The aim of this study is to investigate the effect of three daily fish feeding frequencies, two, four and eight times per day (FF2, FF4, and FF8, respectively) on growth performance of sea bass (Dicentrarchus labrax)and lettuce plants (Lactuca sativa) reared in aquaponics. 171 juvenile sea bass with an average body weight of 6.80 ± 0.095 g were used, together with 24 lettuce plants with an average initial height of 11.78 ± 0.074 cm over a 45-day trial period. FF2 fish group showed a significantly lower final weight, weight gain and specific growth rate than the FF4 and FF8 groups. Voluntary feed intake was similar for all the three feeding frequencies treatmens (p > 0.05). No plant mortality was observed during the 45-day study period. All three aquaponic systems resulted in a similar leaf fresh weight and fresh and dry aerial biomass. The results of the present study showed that the FF4 or FF8 feeding frequency contributes to the more efficient utilization of nutrients for better growth of sea bass adapted to fresh water while successfully supporting plant growth to a marketable biomass.
Keywords: Aquaponics; Feeding frequency; Juvenile sea bass; Lettuce; Water reuse